Synthesis of cadmium-free quantum dots - Aaron, Tan Cheng Shiong (Universiti Sains Malaysia, 2017)
Due to the toxicity issues of cadmium-based quantum dots, there is a need to replace it with cadmium-free quantum dots. In this project, synthesis of zinc selenide quantum dots (ZnSe QD) using hot injection method will be studied. In today’s researches, diethylzinc is used as the zinc precursor. However, diethylzinc possess safety issues in which it reacts violently with water and easily ignites upon contact with air. Therefore, a new material (zinc acetate) was proposed in this project. The precursors were prepared by dissolving zinc acetate and selenium into trioctylphosphine (TOP). They were then injected into two different types of coordinating solvents, that were mixture of trioctylphosphine oxide (TOPO), hexadecylamine (HDA) and tetradecylphosphonic acid (TDPA), and hexadecylamine (HDA) only. Synthesis of ZnSe QD in HDA coordinating solvent was found to be successful. Growth time and molar ratio (Zn:Se) were manipulated to determine the optimum parameters. The optimum parameters to synthesize ZnSe QD were at molar ratio (Zn:Se) of 1:2 and growth time of 15 minutes. Based on the UV-Vis absorbance spectra, the radius of ZnSe QD was calculated by using effective mass approximation and was found to be 3.61 nm in which, it is smaller than the bulk exciton Bohr radius of ZnSe (5.7 nm). Stability study on ZnSe QD showed that the ZnSe QD was stable and did not agglomerate much throughout one month period. The UV-Vis absorption spectra remained at 431 nm throughout the month, indicating that there were no changes in the particle size. Based on zeta potential measurement, ZnSe QD were found to agglomerate (unstable) at first (11.5 mV) and became stable over period of time (-21.1 mV). In conclusion, synthesis of ZnSe QD using zinc acetate as Zn precursor with HDA coordinating solvent was successful.